Upaya Peningkatan Kemampuan Berpikir Kritis Siswa Kelas VII Pada Mata Pelajaran IPS Di Sekolah Menengah Pertama Negeri 2 Kota Bandung Dengan Menerapkan Strategi Pembelajaran Berbasis Masalah - Astri Imaniyati (Peneliti.net, 2018)
The purpose of this study is to improve the critical thinking skills of seventh grade students in BandungSecondary School 2 by implementing problem-based learning strategies (PBL) for social studiessubjects. The method used in this study is action research (Action Research) which refers to the Kemmisand McTaggart models. The result of the research shows that: 1) The implementation of problem-basedlearning strategy (PBL) in social studies subjects in SMP Negeri 2 Bandung can improve students'critical thinking skills, 2) students' critical thinking ability in IPS lesson in SMP Negeri 2 Bandung.through the implementation of problem-based learning strategies (PBLs) can be established throughauthentic inquiry activities, as these activities take place requiring students to find real solutions toproblems that occur in the real world.